(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3CKfGA eGOI Ygf , jbhd cKjQ hEP eYQhagG dc YGgQ jchf GdMGVQ hGdKGHJ s
(3BNQgG (B:s
(3JfJgi CKfGA eGOI WjQ , Hbhdg hGdeWjQ VQH ef GdHQhO bGd CHh MfjaI GdeWjQ gfG VQH ef UfYJg hPgH GHf Lfi Edi Cf GdeWjQ GdYhO hWGQ GdTYQ WGd s
(3fSNI KGdKI YTQI bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B215 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1616s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs